KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI ERA REVOLUSI INDUSTRI 4.0 - Shofwani, Siti Aniqoh; Sundari, Pipit; Sarbullah; Hartarini, Yovita Mumpuni; Hariyadi, Ahmad (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2024)
The aim of this research is to improve the leadership of school principals towards the effectiveness of driving schools in improving the quality of education in the era of industrial revolution 4.0. The research method used to write this article is a qualitative method with a literature review approach. for the development of high school schools in Rembang Regency. Of course, now that we are entering the era of the industrial revolution, the quality of schools must be improved with ideal leadership. Leadership of the industrial revolution 4.0. Leaders who follow technological developments must have the skills to influence, encourage, guide, direct and mobilize other people involved in organizing and developing education and teaching in the era of the industrial revolution 4.0. In other words, the success of a school in achieving its goals really depends on the leadership of the school principal who is able to use all the resources the school has effectively and efficiently. Driving schools change the new paradigm of student-centered learning which embodies the Pancasila student profile which includes competencies and character originating from superior human resources to improve the quality of education in the era of the industrial revolution 4.0.